Pengaruh Kompetensi, Motivasi, dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Sosial - Abrar Hibatullah Hisyam; Hasmawaty AR; Sulaiman Helmi; Trisninawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aimed to asses the partial or simultaneous influence of competence, motivation, and work environment on employee performance at the Dinas Sosial Kabupaten Musi Banyuasin Regency. Using the census approach, the population involved in this study was comprised of 42 Civil Servants from the Office of Sosial in Musi Banyuasin Regency. The data source utilized is primary data acquired via questionnaires distributed to employees. Using the path coefficient data from the Smart PLS 3 program, the validity test, the reliability test, the goodness of fit test, dan the hypothesis test are utilized as the analytical approach. The results indicate that competence, motivation, and work environment have a positive and statistically significant effect on employee performance, therefore all hypotheses can be accepted.